50 health scares that fizzled - Callahan, Joan R. (Greenwood, 2011)
Killer bees. The measles vaccine. Three Mile Island. Artificial sweeteners. The swine flu. All of these health risks and news stories took us by surprise, caused great alarm, and created controversyÑuntil they quietly dropped off our collective radar screens and we forgot about them. What were the real stories behind these health scares?